Od idei do realizacji – Ogrody dziecięce im. W.E. Raua w Warszawie 1899-1901 - Wojewoda , Anna (Studia Edukacyjne, 2019)
In the 19th and 20th centuries the idea of collective games in the open was very popular. The idea of developing physical activity of children was also accepted in the Kingdom of Poland. Drawing inspiration from Germany, Sweden, Belgium and France and inspired by Henryk Jordan Gardens in Krakow, representatives of the Warsaw Hygiene Society decided to set up similar gardens in Warsaw. After the enthusiastic opening of the garden in 1899, they quickly had to interrupt the fun to includ this type of activity in the Society. At that time, being unable to formally conduct collective games, members of the organizing committee were delegated abroad to seek inspiration and organizational and methodical solutions. W.E. Raue Children’s gardens re-started their activity in 1901, after obtaining the consent of the Ministry of the Interior.